STRATEGI PENGEMBANGAN PEMASARAN DIGITAL PRODUK MAKE-UP WARDAH PADA PLATFORM MEDIA SOSIAL - Shalihah, Wardatus; Alyah Irvie Aranda Alben Susanto; Erwin Permana; Harnovinsah, Harnovinsah (Bajang Institute, 2025)
The development of the digital ecosystem has significantly impacted the strengthening of business ecosystems. Since the post-COVID-19 pandemic, the cosmetics industry has become one of the highest-selling sectors. This study aims to analyze the digital marketing development strategy of Wardah makeup products on social media platforms. The research employs a qualitative descriptive approach, with data sourced from observations and digital reviews across various databases and relevant official websites. The findings indicate that Wardah's digital marketing strategy—focusing on engaging visual content, collaborations with influencers, and promotions through e-commerce—has effectively reached its target market. By continuously innovating and adapting to changing consumer behavior in the digital landscape, Wardah can maintain its position as a leading cosmetics brand in Indonesia while meeting the evolving needs of customers. Wardah's success is also supported by a marketing approach that emphasizes visually appealing, interactive content aligned with brand values, as well as a personalization strategy that leverages analytics technology to understand consumer preferences. By staying responsive to the latest digital trends and developing creative methods to attract consumer interest, Wardah continues to strengthen its presence in the competitive cosmetics industry.